Thermoluminescence characteristics of synthetic quartz - Niyonzima, Pontien (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2014)
Quartz is one of the most abundant natural minerals in the crust of the earth. Due to its dosimetric luminescence properties, it is employed in retrospective dosimetry, archaeological and geological dating. The intensity and the structure of the TL glow curves of quartz are strongly dependent upon the origin, impurity content, formation condition and pre-irradiation heat treatment. The aim of this project is to study the mechanisms of thermoluminescence (TL), Phototranssferred thermoluminescence (PTTL) and radioluminescence (RL) in synthetic quartz and to discuss the results in terms of physical characteristics of point defects involved. Thermoluminescence measurements were made on a sample of synthetic quartz in its as-received state (unannealed) synthetic quartz annealed at 500ËšC for 10 minutes. The unannealed sample shows six TL glow peaks located at 94, 116, 176, 212, 280 and 348ËšC at a heating rate of 5ËšCsâ »Â¹. The annealed sample shows seven TL peaks at 115, 148, 214, 246, 300, 348 and 412ËšC at a heating rate of 5ËšCsâ »Â¹. The intensity of peak I, at 94 and 115ËšC for the unannealed and annealed samples respectively, increases with irradiation. Peak I has an activation energy of approximately 0.90 eV and a frequency factor of the order of 10Â¹Â¹ sâ »Â¹. The order of kinetics is between 0.9 and 1.2. The unannealed synthetic quartz shows phototransferred thermoluminescence (PTTL) at the position of peak I after removal of the first three peaks followed by illumination. The PTTL intensities show peak shaped behaviour when plotted against illumination time. The PTTL showed a quadratic increase with dose. The material exhibits fading of PTTL intensity with delay time. Radioluminescence was measured on synthetic quartz unannealed and annealed annealed at 500, 600, 700, 800, 900 and 1000ËšC for 10 to 60 min. The emission spectra of synthetic quartz show seven emission bands. The effect of irradiation on the RL spectra is to increase the intensity of all emission bands for samples annealed at temperatures less than or equal to 700ËšC. The effect of annealing time is to increase the RL amplitude for the samples annealed at temperatures greater than 700ËšC. The annealing temperature increases the RL amplitude of all emission bands of the spectrum for all samples.
Keywords: Thermoluminescence; Quartz; Emission spectroscopy